Older Eastern White Pine Trees and Stands Accumulate Carbon for Many Decades and Maximize Cumulative Carbon - Leverett, Robert T.; Masino, Susan A.; Moomaw, William R. (Frontiers in Forests and Global Change, 2021)
Pre-settlement New England was heavily forested, with trees exceeding 2 m in diameter. The forests have regrown since farm abandonment, representing what is aguably the most successful regional reforestation on record and identified recently in the “Global Safety Net.” Temperate “old-growth” forest and remnant stands demonstrate that native tree species can live several hundred years and continue to add to forest biomass and structural and ecological complexity. Forests globally are an essential natural climate solution that accumulate carbon and reduce annual increases in atmospheric CO2 by approximately 30%. Some studies emphasize young, fast-growing trees and forests while others highlight carbon storage and accumulation in old trees and intact forests. We addressed this directly within New England with long-term, accurate field measurements and volume modeling of individual trees and two stands of eastern white pines (Pinaceae: Pinus strobus) and compared our results to models developed by the U.S. Forest Service. Within this sample and species, our major findings complement and clarify previous findings and are three-fold: 1) beyond 80 years, an intact eastern white pine forest can accumulate carbon above-ground in living trees at a high rate and double the carbon stored in this compartment in subsequent years; 2) large trees dominate above-ground carbon and can continue to accumulate carbon; 3) productive stands can continue to sequester high amounts of carbon in live trees for well over 150 years. Because the next decades are critical in addressing the climate crisis, and most New England forests are less than 100 years old, a major implication of this work is that maintaining and accumulating carbon in some existing forests – proforestation – is a powerful regional climate solution. Furthermore, older and old-growth trees and forests are rare, complex, highly dynamic and biodiverse: dedication of some forests to proforestation will produce large carbon-dense trees and also protect ecosystem integrity, special habitats, and native biodiversity long-term. In sum, strategic policies to grow and protect suitable existing forests in New England will optimize a proven, low cost, natural climate solution that also protects and restores biodiversity across the landscape.